Synthetic Hydrogel Dilutes Serratia plymuthica Growth— Promoting Effect on Brassica napus L. Under Drought Conditions - Grażyna B. Dąbrowska; Daniel Krauklis; Milena Kulasek; Magdalena Nocny; Marcel Antoszewski; Agnieszka Mierek-Adamska; Beata Kaliska (Agriculture)
Progressive climate change increases drought frequency, severely impacting crop growth and yield. New eco-friendly alternatives to chemical protection agents and fertilisers are needed to reduce pollution and enhance plant health. This study evaluated the effects of the plant growth-promoting rhizobacteria (PGPR) and the hydrogel (potassium polyacrylate) on Brassica napus L. during drought conditions. After in vitro and pot experiments, Serratia plymuthica was selected from six PGPR candidates based on its ability to enhance plant biomass, shoot length, and number of internodes. The seed viability test, reactive oxygen species accumulation, and SOD activity showed no adverse effects of applying hydrogel to canola seeds. Moreover, the hydrogel did not show toxicity towards tested bacterial strains. Field trials during the drought demonstrated that inoculation with S. plymuthica significantly increased the number of siliques (16.48%) and yield (19.93%), compared to controls. Plants grown from inoculated seeds were also taller (3.28%) and had more branches (39.99%). We also analysed seedling emergence, number of internodes, thousand seeds’ weight, and seed moisture. The hydrogel applied to the soil delayed seedling emergence and dampened the growth-promoting effect of S. plymuthica, resulting in reduced yield. Compared with plants inoculated with S. plymuthica, there was a decrease in the yield of plants treated solely with hydrogel and in plants treated with hydrogel and the bacterium of 23.61% and 27.79%, respectively. Our results indicate that S. plymuthica has a high potential for use in commercial canola farming, especially as an ingredient added to seed coatings.